Methods of exploration and analysis of the urban spatial structure of cities/ comparative studies - مغرقونه, مرح (Latakia University Journal -Engineering Sciences Series, 2023)
The study of urban spatial structure is currently one of the most popular areas of research in urban disciplines, where its study has spread widely nowadays. Also, the rapid development of the city can lead to many problems such as the expansion of the urban scale without planning, which can affect many major issues such as the function of the city. Previous studies have focused on sectional urban systems, thus evaluating urban spatial structure at a specific point in time only while these structures are characterized by constant evolution and change, so this research aims to develop a conceptual framework for “urban spatial structure”, and to clarify and explore this term, to provide context for analysis Experimental, contributes to the characterization of this structure in the studied urban area and then investigates its development patterns. The research began according to a scientific sequence by conducting a review of the most important literature related to the urban spatial structure of cities, the most important factors affecting it, and ways to determine this structure and its changes. Then a comparative study of a group of global studies that dealt with the urban spatial structure of cities with various tools and methods of analysis. The research found, through study and analysis, the diversity of methods used in determining the urban spatial structure of cities, where the availability and nature of data plays the main role in determining the structural and sub-dimensions of the framework used in this study. It was also shown that the study of urban spatial structure requires an approach with a set of tools to better understand how these measures interact across an urban area to influence outcome variables and thus the resulting urban spatial structure. The research recommended the need to combine traditional methods and tools, big data and advanced analytical programs within urban spatial structure studies to reach the most accurate results, which need empirical enrichment and theoretical expansion.